Fatty acid composition of Swedish bakery products, with emphasis on trans-fatty acids. (15th May 2015) - Trattner, Sofia; Becker, Wulf; Wretling, Sören; Öhrvik, Veronica; Mattisson, Irene
Highlights: Nutrition recommendations emphasise limitation of dietary intake of trans -fatty acids (TFA). Fatty acid composition was analysed in sweet bakery products on the Swedish market. Mean TFA levels were 0.7% of total fatty acids 2007. TFA content has decreased in this product category since 1995–97. Abstract: Trans -fatty acids (TFA) have been associated with increased risk of coronary heart disease, by affecting blood lipids and inflammation factors. Current nutrition recommendations emphasise a limitation of dietary TFA intake. The aim of this study was to investigate fatty acid composition in sweet bakery products, with emphasis on TFA, on the Swedish market and compare fatty acid composition over time. Products were sampled in 2001, 2006 and 2007 and analysed for fatty acid composition by using GC. Mean TFA levels were 0.7% in 2007 and 5.9% in 2001 of total fatty acids. In 1995–97, mean TFA level was 14.3%. In 2007, 3 of 41 products had TFA levels above 2% of total fatty acids. TFA content had decreased in this product category, while the proportion of saturated (SFA) and polyunsaturated (PUFA) fatty acids had increased, mostly through increased levels of 16:0 and 18:2 n-6, respectively. The total fat content remained largely unchanged.